Internationalism Hits the Opera Stage: Nixon (and Dewey) in China (ESPES The Slovak Journal of Aesthetics, 2025)
John Adams’s Nixon in China (1987) is one of the most iconic operatic works of the end of the 20th century. It is also an interesting case to study the relationship between aesthetics and politics. In this paper, I offer a reading of the political and aesthetic sides of the work in light of John Dewey’s philosophy. Central to my account is to examine the effect that Dewey’s own trip to China had on his political philosophy. I argue that Nixon is not just a series of anecdotes related to Nixon’s 1972 visit to China, as has been claimed by some critics, but that the Deweyan perspective I take particularly on Nixon‘s third act shows that the opera has genuine political substance, which is also tied to the work’s aesthetic features.
Keywords: Adams; Dewey; Opera; Politics; Aesthetics